2019
DOI: 10.1074/mcp.ra119.001361
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Maps of Human Gastrointestinal Stromal Tumor Subgroups*

Abstract: Quantitative proteome profiling of GIST from 13 patients classified into very low/low, intermediate and high-risk subgroups were performed. An extended cohort of GIST (n ϭ 131) was used for immunohistochemical validation of proteins of interest. Functional insights into proteins associated with GIST risk grade were assessed. Immunohistochemical analysis revealed that GIST patients with high PTPN1 had low chances of developing metastasis. This work provides valuable information for understanding the inherent bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Relative quantification of identified proteins was determined according to the weighted ratios of the uniquely identified peptides that belonged to a specific protein. Parameters for protein identification and quantification were as previously reported 40 , except the false discovery rate (FDR) was ≤ 1%. A paired t test was performed to determine statistical significance between the DUGL and AGL.…”
Section: Methodsmentioning
confidence: 99%
“…Relative quantification of identified proteins was determined according to the weighted ratios of the uniquely identified peptides that belonged to a specific protein. Parameters for protein identification and quantification were as previously reported 40 , except the false discovery rate (FDR) was ≤ 1%. A paired t test was performed to determine statistical significance between the DUGL and AGL.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is important to identify novel therapeutic targets for GISTs. In 2019, Liu et al reported proteomics maps of human GISTs and indicated that patients with high PTPN1 expression had low risk of developing metastasis [ 22 ]. However, the global alteration of protein post-translational modifications in GISTs has been yet unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Relative quantification of identified proteins was determined according to the weighted ratios of the uniquely identified peptides that belonged to a specific protein. Parameters for protein identification and quantification were as previously reported [14], except the false discovery rate (FDR) was ≤ 1%. A paired t test was performed to determine statistical significance between the DUGL and AGL.…”
Section: Protein Identification and Quantificationmentioning
confidence: 99%